Medianoche, a Bolero with a Different Language for an Encounter without Limits (Palimpsesto, 2023)
The bolero Medianoche (Manns/Salinas, 1996) is a musical piece that shows a high quality not only in its lyrics but also in its music. Interpreted by the Inti Illimani musical group, this bolero has been very well received by the public, however, in spite of that, it has not had a deserved success at the international level. The comparison with other representative pieces of this gender offers evidence of unique features that show a superior lyric than many traditional boleros; on the other hand, its success, although important, is not comparable to many other boleros' success. The analysis discusses reasons that could explain this fact: The sociocultural context in which Manns/Salinas' bolero appeared, the social commitment of both the lyric and the music composers, and the language used. This last characteristic, which is precisely the main reason for its high quality, could explain the hard road that this bolero has had to follow to gain acceptance by all kinds of public. The language used by Medianoche is the main difference between Medianoche and traditional boleros.
Keywords: Bolero; Medianoche; Patricio Manns; Inti Illimani; dictatorship